2009
DOI: 10.1007/s00421-009-1017-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of menstrual cycle, oral contraception, and training on exercise-induced changes in circulating DHEA-sulphate and testosterone in young women

Abstract: The objective of this study was to ascertain the effects of menstrual cycle, oral contraception, and training status on the exercise-induced changes in circulating DHEA-sulphate and testosterone in young women. Twenty-eight healthy women were assigned to an untrained group (n = 16) or a trained group (n = 12) depending on their training background. The untrained group was composed of nine oral contraceptive users (OC+) and seven eumenorrheic women (OC-). The trained group was composed of OC+ subjects only. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 42 publications
3
20
1
Order By: Relevance
“…The tT results confirmed and agree with the results of previous studies (3,8). That is, there was no major impact on the tT responses as a result of menstrual phase, only that of exercise.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The tT results confirmed and agree with the results of previous studies (3,8). That is, there was no major impact on the tT responses as a result of menstrual phase, only that of exercise.…”
Section: Discussionsupporting
confidence: 91%
“…As previous research has shown, tT exhibits similar increases to a prolonged bout of aerobic exercise regardless of phase (3,8). However, this study shows a more robust increase in the amplitude of fT responses (absolute and relative) during the H-EP luteal phase of the menstrual cycle.…”
Section: Discussionsupporting
confidence: 71%
“…19,20,39 The type of protocol used in this research can be stated because of inconsistent results, in addition to the synthesis of neurotransmitters' testosterone production (ARs) regarding the power of the synthesis of contractile proteins. 14,22,23 Increased testosterone in response to resistance training appears to be related to the level of increase in the number of androgen receptors (ARs) in human cells.…”
Section: Discussionmentioning
confidence: 99%
“…21 It seems that testosterone and cortisol respond to higher intensity and longer duration of activity. 22,23 High-intensity training protocols involving large muscles acutely increase testosterone level, 24 and also when the exercise intensity decreases from 70% to 40%, hormonal responses decrease in both sexes. 25 Testosterone secretion of glucocorticoids depends on especially cortisol synthesis.…”
mentioning
confidence: 99%
“…The response of testosterone levels to ST may expose the skeletal musculature to an elevated peripheral hormonal concentration, which may improve the interaction between the hormone and its cellular receptors (Hoffman et al, 2003, Willoughby & Taylor, 2004. Regarding aerobic training, even though the importance of the anabolic hormone response remains unclear, it seems that testosterone is more responsive to higher intensity exercises (Enea et al, 2009) and a longer duration of exercises (Harris et al, 1989;Trembley et al, 2005).…”
Section: Acute Testosterone Responses To Physical Exercisementioning
confidence: 99%